A bottom up approach to slowing fashion: Tailored solutions for consumers. (10th May 2021) - West, Jodie; Saunders, Clare; Willet, Joanie
Abstract: Fast fashion has emerged in the last few decades, clothes have become cheaper, less durable and are purchased more frequently. Shifting consumers away from fast fashion is challenging, even for the more ethically minded. Individuals have different decisionmaking practices and respond differently to social norms. Even the most ethically minded engage in 'grey' consumption and are susceptible to planned obsolescence in fashion cycles (McDonald et al., 2012). There is, thus, a value-action gap in relation to clothing where environmental consciousness does not cohere with behaviours. In this paper we use cultural thematic schemata (from cultural theory) as a heuristic device to tailor solutions that could reduce the value-action-gap in relation to sustainable clothing based in-depth qualitative research. Recognising that consumers differ from one another, we suggest targeting the three 'ideal types' of personality derived from cultural theory - the egalitarian, the hierarchist and individualist. It is evident from the findings that bottom-up solutions such as making stations, social marketing, wardrobe audits and education are important enablers of slow fashion. They would work alongside a number of industry-led governmental and top down policies. Our novel use of cultural theory to the problem of fast fashion has enabled us to suggest bottom-up solutions, which can be tailored for maximum resonance with a broad range of people. It was clear for the huge majority of our research participants that social interaction was as important in shaping their views and behaviours as the learning of skills. This should be mimicked in any attempt to increase the life of, or upscale our work. Finding ways of expanding our project work from a small niche, to a mass market is crucial.